FAKTOR YANG MEMPENGARUHI TENAGA KERJA MELAKUKAN MIGRASI COMMUTER DARI SIDOARJO KE KOTA SURABAYA - Adinda Angelina; Nanik Istiyani; Fajar Wahyu Prianto; Rafael Purtomo Somaji; Herman Cahyo Diartho (Study Program of Management Faculty of Economics and Business University of Jember, 2022)
This study aims to analyze factors that can affect the interest of workers to migrate commuters from Sidoarjo to the city of Surabaya. This research aims to analyze the influence of family dependents, education level, income, and marital status on the interest of workers migrating commuters from Sidoarjo to Surabaya City. To achieve this goal in this study, logistic regression model analysis techniques were used using primary data from a sample of 50 respondents. The results of the analysis test of this study showed that the variable burden of family dependents, variables of education level and marital status had a positive and significant effect. While the income variable has a positive and insignificant effect on the interest of the workforce to migrate commuters from Sidoarjo to the city of Surabaya.